Understanding human behavior - Mynatt, Clifford R. (Allyn and Bacon, 2002)
This book takes a unique approach to introductory psychology with 44 short chapters that emphasize the science and evolution of human behavior in a readable, witty, and conceptual manner. Each short chapter is organized around a single idea that relates to psychology and lifelong learning skills (take a look at the Table of Contents). The book engages the readers by ideas and concepts and doesn't overwhelm with lists and terms. For anyone interested in learning the fundamentals of psychology.